Resilience in rural settlements:: an experience in northen Mato Grosso (Sustainability in Debate, 2016)
The aim of the study was adapt the resilience assessment methodology as a tool for strategic and operational planning of Instituto Ouro Verde (IOV), a nongovernmental organization that works to support family-based groups and farmers in northern Mato Grosso. The study was conducted in 04 stages: characterization of the family farmers production system, characterization of the groups involved in IOV, construction of future scenarios for family-based agriculture and developing strategies for action at different levels. The results pointed to the characterization of the family production mode from 04 dimensions: production matrix, work organization, perception of the role of the land and, finally, social organization, evidencing the existing variety of the family farming segment. From this diversity, the actions were set at different scales for the strengthening of the attributes considered essential for these farmers.